Evaluation of Design Features and Technical Characteristics of Power Tillers for Efficient Operation on Private Household Plots (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The article presents the results of an agro-engineering assessment of walk-behind tractors (motoblocks) available on the modern Ukrainian market of small-scale agricultural machinery, taking into account their structural and technological features, operational parameters, and functional capabilities. The relevance of using walk-behind tractors as an effective means of mechanizing technological processes in household and small-scale farming under the conditions of transformation of Ukraine’s agri-food sector has been substantiated.A comparative analysis of the technical characteristics of motoblock models of various classes — from light to heavy — differing in weight, engine power, type of gearbox, and compatibility with mounted equipment has been conducted. The study examines the design features of belt-driven, direct-drive, and gearbox-type motoblocks, as well as the influence of engine type (gasoline or diesel) on performance, fuel efficiency, and operational convenience.The research identifies the main criteria for selecting a motoblock for effective operation on small land plots: energy performance, transmission reliability, working width of soil tillage implements, ergonomic control features, and the possibility of using a wide range of attachments.Motoblocks have been classified according to weight and engine power into four groups, which allows users to reasonably select the optimal model based on soil and climatic conditions and the type of technological operations.Based on the analysis results, recommendations are proposed regarding the selection, operation, and maintenance of motoblocks, taking into account energy, economic, and ergonomic criteria.The obtained results have practical significance for owners of household and small-scale farms and can also be used in the educational process for training agro-engineering specialists to develop competencies in the field of operation of small mechanized agricultural machinery.
Keywords: walk-behind tractor; small-scale machinery; agro-engineering assessment; soil tillage; productivity